'Because their patron never dies': ecclesiastical freedmen, socio‐religious interaction, and group formation under the aegis of 'church property' in the early medieval west (sixth to eleventh centuries). Issue 4 (14th October 2021) - Esders, Stefan
Abstract : In the early medieval west, patronate, as adapted from Roman law, was a fundamental category in determining the legal status of freedmen. In many cases it entailed a basic set of obligations. In an increasing number of situations, however, the patron became an ecclesiastical institution, since slaves and freed persons were often given to churches and monasteries. As ecclesiastical institutions regarded their patronal rights over freed persons as part of inalienable church property, the patronal relationship became permanent and inheritable. In Eastern Francia (the Rhineland and beyond) this transformed ecclesiastical freedmen into religiously defined social groups with potentially distinct aims, religious tasks, and organizational structures, and a shared notion of freedom. From the Carolingian period onward, it even became attractive to enter voluntarily into this status. It is argued here that with its underlying network of socio‐religious relations, patronate over ecclesiastical freedmen and censuales can be better understood when considered as an element of a 'temple society' .